Unraveling the effects of added Chuzhou chrysanthemum polysaccharides on the structure and physicochemical properties of instant kudzu starch: An interactive perspective - Ruidi He; Chengjin Liu; Xinyi Wang; Pengli Hu; Liping Yang (Food Research International, 2026)

Unveiling the impact of 2D/3D urban morphology on thermal comfort across urban-rural gradients using machine learning - Chunguang Hu; Yuxuan Tao; Maomao Zhang; Houbao Fan; Nan Xu; Yucheng Sun; Ruidi Yuan; Jianqing Zhao (Energy and Buildings, 2025)

Investigating the quantitative impact of the vegetation indices on the urban thermal comfort based on machine learning: A case study of the Qinhuai River Basin, China - Jianqing Zhao; Chunguang Hu; Zhuoqi Li; Maomao Zhang; Houbao Fan; Kaili Li; Ruidi Yuan (Sustainable Cities and Society, 2025)

Reduce pollution, establish protected areas, manage fisheries properly? How to protect coral reefs based on carbon trading - Yuntao Bai; Ruidi Hu; Lan Wang; Delong Li (Frontiers in Marine Science, 2024)
As coral reefs around the world have suffered serious damage, it is necessary to protect them. Common modes of coral reef protection include reducing pollution, setting up reserves and managing fisheries rationally. In order to derive the applicable scope of various protection modes for coral reefs, this article constructs three differential game models and compares and analyzes the equilibrium results obtained by the models. Finally, the study shows that whether for developed or developing countries, when the benefits of coral reef treatment are small, the mode of reducing pollution can achieve the maximum benefit. As the benefits of coral reef treatment gradually increase, the mode of setting up nature reserves can achieve the maximum benefit. It is worth noting that the greater the carbon emission rights obtained by the number of coral reefs, the greater the benefits of coral reef treatment, the more likely developed countries will adopt the mode of setting up reserves.

Free-surface undulation and velocity turbulence in shallow undular hydraulic jumps - Hong Hu; Hang Wang; Dongzi Pan; Xiekang Wang; Ruidi Bai (Ocean Engineering, 2023)